Problem of Midwives to Referral Patients for Sectio Caesarea in PPK II BPJS in Bantul Region, 2020 - Yuni Fitriana; Ari Andriyani; Andina Vita Sutanto (Universitas Katolik Soegijapranata Semarang, 2021)
Abstract: Every woman wants to have a baby safely. Delivery can be normal or Section Cesaria (SC). Midwives who experience complications are referred to by the midwife as PPK I to the PPK II BPJS Hospital. SC measures include BPJS Health capitation. The referral flow is regulated by the National Health system which is divided into first-level health services (PPK I). and advanced level (PPK II). The implementation of the referral still encountered problems in PPK II such as patient refusal. This research is a qualitative descriptive study with an empirical judicial approach, namely analyzing the process of patient referral for SC measures related to BPJS, collaboration between midwives and PPK II BPJS, obstacles and problem solving for patient referral for SC action. The results of the SC action research are based on medical indications, the referral process from PPK I to PPK II has no obstacles in accordance with the rules and uses the BPJS SISRUTE, Midwives do not get fees for referring BPJS patients in PPK II, obstacles in the form of requests for BPJS class advancement, financing claims BPJS is sometimes jammed, the patient refuses to be referred because the room is not available. Resolving these obstacles requires the socialization of BPJS regulations, regular financial management, and the maximum use of SISRUTE. Therefore the need for the Government to always improve the quality of BPJS services with clear regulations.Abstrak: Setiap perempuan ingin melahirkan bayi dengan aman. Persalinan dapat secara normal atau Section Cesaria (SC). Persalinan yang mengalami penyulit dirujuk Bidan sebagai PPK I ke Rumah sakit PPK II BPJS. Tindakan SC termasuk kapitasi BPJS Kesehatan. Alur rujukan diatur oleh sistem Kesehatan Nasional yang terbagi menjadi pelayanan Kesehatan tingkat pertama (PPK I). dan tingkat lanjutan (PPK II). Pelaksanaan rujukan tersebut masih menemui masalah di PPK II seperti adanya penolakan pasien. Penelitian ini merupakan penelitian deskriptif kualitatif dengan pendekatan yudiris empiris yakni menganalisis proses rujukan pasien tindakan SC terkait BPJS, Kerjasama bidan dengan PPK II BPJS, Hambatan dan penyelesaian masalah rujukan pasien tindakan SC. Hasil penelitian Tindakan SC didasarkan pada indikasi medis, proses rujukan dari PPK I ke PPK II tidak ada kendala sudah sesuai dengan aturan dan menggunakan SISRUTE BPJS, Bidan tidak mendapatkan pembayaran tambahan (fee) dalam merujuk pasien BPJS di PPK II, hambatan berupa permintaan naik kelas BPJS, klaim pembiayaan BPJS yang kadang macet, adanya penolakan pasien dirujuk dengan alasan ruangan tidak tersedia. Penyelesaian hambatan tersebut perlunya sosialisasi aturan BPJS, manajemen keuangan yang teratur, penggunaan SISRUTE secara maksimal. Oleh karena itu perlunya Pemerintah selalu melakukan peningkatan kualitas pelayanan BPJS dengan regulasi yang jelas.